2018
DOI: 10.26434/chemrxiv.7019579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Conserved Asparagine in a Ubiquitin Conjugating Enzyme Positions the Substrate for Nucleophilic Attack

Abstract: We present classical molecular dynamics (MD), Born-Oppenheimer molecular dynamics (BOMD), and hybrid quantum mechanics/molecular mechanics (QM/MM) data. MD was performed using the GPU accelerated pmemd module of the AMBER14MD package. BOMD was performed using CP2K version 2.6. The reaction rates in BOMD were accelerated using the Metadynamics method. QM/MM was performed using ONIOM in the Gaussian09 suite of programs. Relevant input files for BOMD and QM/MM are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Based on the alignment in Fig 2A, the putative catalytic cysteine of UBC2 is C85, equivalent to C87 in S. cerevisiae UBC13 and C87 in human UBE2N (35). UBC2 also contains an HPN motif 10 amino acids Nterminal of C85 that may be involved in catalysis (28)(29)(30). All of the proteins in the UEV1 alignment ( Fig 2B) lack catalytic cysteine residues and HPN motifs, consistent with UEV1 being part of the noncatalytic UEV family of E2s (27).…”
Section: Ubc2 and Uev1 Are Orthologues Of Human Ube2n And Ube2v1/ube2v2mentioning
confidence: 72%
See 2 more Smart Citations
“…Based on the alignment in Fig 2A, the putative catalytic cysteine of UBC2 is C85, equivalent to C87 in S. cerevisiae UBC13 and C87 in human UBE2N (35). UBC2 also contains an HPN motif 10 amino acids Nterminal of C85 that may be involved in catalysis (28)(29)(30). All of the proteins in the UEV1 alignment ( Fig 2B) lack catalytic cysteine residues and HPN motifs, consistent with UEV1 being part of the noncatalytic UEV family of E2s (27).…”
Section: Ubc2 and Uev1 Are Orthologues Of Human Ube2n And Ube2v1/ube2v2mentioning
confidence: 72%
“…Furthermore, the HPN (His-Pro-Asn) motif, which is conserved in human E2-conjugating enzymes and which contains an asparagine residue that can be important for catalysis (28)(29)(30), was found to be partially or completely missing in UBC3, UBC6, UBC11, UBC14 and UEV1. A HECT domain alignment for L. mexicana HECT E3 ligases and 4 human HECT E3 ligases showed that HECTs 1-12 contained the conserved catalytic cysteine residue.…”
Section: Ubiquitination Gene Families In L Mexicanamentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the alignment in Fig 2A, the putative catalytic cysteine of UBC2 is C85, equivalent to C87 in S. cerevisiae UBC13 and C87 in human UBE2N [39]. UBC2 also contains an HPN motif 10 amino acids N-terminal of C85 that may be involved in catalysis [31][32][33]. All of the proteins in the UEV1 alignment ( Fig 2B) lack catalytic cysteine residues and HPN motifs, consistent with UEV1 being part of the noncatalytic UEV family of E2s [30].…”
Section: Plos Pathogensmentioning
confidence: 72%
“…Similarly, an alignment of L. mexicana and human E2-conjugating enzymes showed conservation of the conserved catalytic cysteine in all L. mexicana E2s except UEV1 (S1B Fig), suggesting the latter is a non-catalytic ubiquitin E2 variant [30]. Furthermore, the HPN (His-Pro-Asn) motif, which is conserved in human E2-conjugating enzymes and which contains an asparagine residue that can be important for catalysis [31][32][33], was found to be partially or completely missing in UBC3, UBC6, UBC11, UBC14 and UEV1. A HECT domain alignment for L. mexicana HECT E3 ligases and 4 human HECT E3 ligases showed that HECTs 1-12 contained the conserved catalytic cysteine residue.…”
Section: Plos Pathogensmentioning
confidence: 89%